SELF-REGULATED LEARNING IN BUTET MANURUNG’S THE JUNGLE SCHOOL - Eka Mulatsih, Maria Vincentia; Aurora, Vincentia Devina (IJIET (International Journal of Indonesian Education and Teaching), 2021)
Education is an essential aspect of a community development. In Indonesia, various educational changes have been done in order to cater students with the necessary skills to face the vast dynamics of the world. Despite those changes integrated into the curriculum, Indonesia still has an issue to provide suitable learning processes for students who live in some remote areas during pandemic. Butet Manurung’s the Jungle School portrays some efforts for helping “Orang Rimba”, the nomadic tribes who live in rainforests at Bukit Dua Belas to experience proper education. Focusing on some learning processes in the work, a document analysis was combined with a theory of education. Then, the researchers found that self-regulated learning concepts were applied. This self-regulated learning took form in three aspects that were done by jungle children and this could be one of the keys to face some learning problems in some remote areas during pandemic.